2012
DOI: 10.1002/jbm.a.34535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic inflammation and immune response on regeneration induced by decellularized bovine pericardium

Abstract: Decellularised tissue produces a variety of host responses ranging from constructive remodeling to scarring on account of its differences in the source of tissue, processing or sterilization methods. In this study, in vivo regeneration induced by decellularised bovine pericardium with or without mild glutaraldehyde crosslinking was studied in relation to its immune and inflammatory response using rat abdominal regeneration model. Mild glutaraldehyde crosslinking was done to subdue inflammatory and immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Commercially available GTA cross-linked tissue grafts (Table 3) (Peri-Guard ® Repair Patch, Synovis, denaturation temperature 83 °C 139 ) have been shown to elicit chronic inflammation and typical foreign reaction, as evidenced by the early dense accumulation of mononuclear cells and the prolonged presence of macrophages, FBGCs and fibrous encapsulation surrounding the implant 149,157,158 . GTA cross-linked bovine pericardium grafts reduced M2/M1 macrophage ratio during inflammation phase, as compared to non-cross-linked grafts 159 . Moreover, non-commercial GTA cross-linked sheep collagen disks induced a massive infiltration of neutrophils that secreted a high amount of MIP-1, MCP-1 and IFN-γ, recruiting and activating macrophages.…”
Section: In Vivo Assessment Of Host Response To Collagen-based Devicesmentioning
confidence: 99%
“…Commercially available GTA cross-linked tissue grafts (Table 3) (Peri-Guard ® Repair Patch, Synovis, denaturation temperature 83 °C 139 ) have been shown to elicit chronic inflammation and typical foreign reaction, as evidenced by the early dense accumulation of mononuclear cells and the prolonged presence of macrophages, FBGCs and fibrous encapsulation surrounding the implant 149,157,158 . GTA cross-linked bovine pericardium grafts reduced M2/M1 macrophage ratio during inflammation phase, as compared to non-cross-linked grafts 159 . Moreover, non-commercial GTA cross-linked sheep collagen disks induced a massive infiltration of neutrophils that secreted a high amount of MIP-1, MCP-1 and IFN-γ, recruiting and activating macrophages.…”
Section: In Vivo Assessment Of Host Response To Collagen-based Devicesmentioning
confidence: 99%
“…Finally, Bayrak et al [78] found that decellularized porcine pulmonary heart valves promote T cell proliferation and activation. Recent work in macrophage polarization has described two macrophage phenotypes in host response: M1 macrophages which are effectors of the pro-inflammatory degenerative response and M2 macrophages which have been linked to a regenerative response following tissue damage [44, 8587]. Identification of M2 macrophages suggests the possibility of a benefit to the inflammatory response in tissue regeneration, an area under much investigation.…”
Section: Decellularizationmentioning
confidence: 99%
“…Among the infiltrated macrophages, M1 phenotype is reported to be proinflammatory cytotoxic macrophage, which is associated with classic signs of inflammation, whereas the anti‐inflammatory macrophage M2 promotes immunoregulation, tissue repair, and constructive remodeling . Uncross‐linked decellularised bovine pericardium was shown to elicit M2 macrophage response in rat abdominal implantation, whereas mildly cross‐linked bovine pericardium used in this study elicited M2 macrophage response only at shorter duration . Monocyte infiltration into the graft has also been shown to promote VEGF expression within the scaffold throughout the duration of macrophage infiltration, which was beneficial to healing .…”
Section: Discussionmentioning
confidence: 66%
“…Decellularized tissue was shown to promote remodeling of the prosthesis by neovascularization and recellularization by the host . Decellularized bovine pericardium was also shown to elicit M2 macrophage response favorable for regeneration besides causing significantly reduced humoral and cell mediated immune response . Decellularization is a critical process, and inadequate procedure may lead to undesirable results, such as calcification and immune reaction on account of removal of tightly bound proteoglycans causing loss of collagen–proteoglycan interactions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation